Pemberdayaan Poktan Pengolahan Teh Hijau melalui Aplikasi Teknologi Penggulung Teh Berbasis IOT - Riyadi Muslim; Cahyaningtyas Putri Suhita; Herman Saputro; Laila Fitriana (Yayasan Literasi Sains Indonesia, 2025)
The revitalization of green tea production technology plays a pivotal role in fostering the enhancement of the quality and competitiveness of local products in Indonesia. Although Indonesia's green tea export earnings reached 69.01 million USD in 2023, this figure remains low compared to neighboring countries. Competitive trade in the global tea market requires improved production processing technology. This paper explains how the application of IoT-based green tea rolling technology can empower Poktan communities and align with the government's revitalization program. This community empowerment method is divided into six stages: 1). Preparation and production planning 2) Tool and Innovation Concept Development, 3) Innovation design, 4) Implementation, 5) Marketing digitalization, 6) Evaluation. This step is a breakthrough that will allow us to continue to be competitive by meeting the needs of consumers globally. Furthermore, the use of modern technology will help achieve SDG 7 (affordable and clean energy), SDG 9 (industry, innovation, and infrastructure), and SDG 13 (climate action) in the future.